Interview with John Tonkin, artist, Bondi Junction, Sydney, Australia, 21 April 2013 - Messham-Muir, Kit (2014)
John Tonkin is a new media artist based in Sydney. He works primarily with responsive video installations, in which the imagery will respond directly to the movement and proximity of the viewer in the gallery. I met John in his home and studio in Sydney and talked about the role of new media in art today, how the term "new media" is itself problematic, and John’s thoughts around how we think we think about thinking.